Tanda Identitas Dan Simbolisme: Analisis Perlakuan Pengibaran Bendera Dalam Konteks Hubungan Bilateral Indonesia-Palestina - Shifa Amelia Nur; Lusiana Vilya Chalisyah; Anjanika Puspa Kenanga; Maulia Depriya Kembara (Jurnal Relasi Publik, 2024)
This research is motivated by the phenomenon that attracted the attention of netizens due to the raising of the Red and White Flag which was raised together with the flag of the Palestinian state which was spread through twitter social media. Many of the platform users commented that the incident was not in accordance with the laws and regulations in Indonesia. In collecting data, this study used quantitative methods by examining the subject population of high school and university students with a survey approach. This study shows the subject's attention to the treatment of his country's identity, namely the Indonesian national flag as a student. The obligation to defend the country in the form of respect for the Indonesian national flag should be instilled in every soul of the young generation of the Indonesian nation. State defense is not only an obligation but also for the sake of maintaining the continuity of the Indonesian nation as a Pancasila human being.